Pandemic COVID-19 Diseases and Rajyakshma in Charak Samhita: A conceptual study - Nishi Arora (Wolters Kluwer Medknow Publications, 2020)
Introduction: This paper correlates the vastly detailed concepts of Janpadod dhwans and Rajyakshma from Charak Samhita to the novel coronavirus. The aim of this paper is to draw the attention of the experts toward the similarities between coronavirus and Rajyakshma, in hopes of finding some more effective measures of prevention as well as cure for the ongoing pandemic. Materials and Methods: In this paper, a little description was given about Adharm and immunity. The concept of pandemic/epidemic is explained with the term "Janpadod dhwans." A detailed comprehensive exploration of corona versus Rajyakshma was done by thoroughly analyzing certain concepts in the ancient script Charak Samhita and by conducting meticulous research online. Results: It was deduced that every disease changes its mode of onset and course of progression with changing climatic conditions and timeline peculiarities. The diseases are not identical, but the author hopes that the similarities drawn can be of use to better understand the whole spectra of diseases that have come and those that have yet to come. Conclusion: A clear conclusion can be drawn that there are many similarities between COVID-19 and Rajyakshma in clinical presentation, as well as the preventive measures known so far. The role of good immunity is the key factor in both the cases.